2019
DOI: 10.1021/acs.jpcc.8b11239
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrates on the Photoelectrochemical Performances of Ag2ZnSnSe4 Thin Films

Abstract: This work describes the photoelectrochemical (PEC) performance of Ag 2 ZnSnSe 4 (AZTSe) thin films prepared on various conductive substrates such as Al, Cu, Ag, and conventional glass by a thermal evaporation method. The X-ray diffraction analysis confirms that the deposited films are the pure tetragonal structure of AZTSe. The scanning electron microscope (SEM) images show polygonal-shaped and spherical-rich particles, which are uniformly distributed over the substrates and are densely packed. By comparing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…The values of these regions are tabulated in Table 3. Fill factor ((V max J max /V oc J sc ) x 100)) and photoconversion e ciency ((η (%) = (V oc J sc x FF x 100) / P in )) are calculated using the formulae [50] and the values are given in table 4. From gure 16 it is observed that all the lms exhibited cathodic photocurrent which leads to the reduction of the hole scavenger at the surface of the working electrode that con rms that the prepared Ag x Bi 2-x S 3-y (x= y= 0.25, 0.50, 0.75 and 1) thin lms are 'p' type in nature [2,51,37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The values of these regions are tabulated in Table 3. Fill factor ((V max J max /V oc J sc ) x 100)) and photoconversion e ciency ((η (%) = (V oc J sc x FF x 100) / P in )) are calculated using the formulae [50] and the values are given in table 4. From gure 16 it is observed that all the lms exhibited cathodic photocurrent which leads to the reduction of the hole scavenger at the surface of the working electrode that con rms that the prepared Ag x Bi 2-x S 3-y (x= y= 0.25, 0.50, 0.75 and 1) thin lms are 'p' type in nature [2,51,37].…”
Section: Resultsmentioning
confidence: 99%
“…The values of these regions are tabulated in Table 3. [50] and it is presented in Table 3. The carrier concentration of FTO/Ag x Bi 2-x S 3-y (x= y = 0) lm is found to be 6.23 x10 19 cm -3 which is well accordance with Hall effect analysis (table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peaks observed at 181 and 250 cm −1 reveal the formation of AZTSe and ZnSe phases, respectively . Till date, not many reports are available on the Raman analysis of AZTSe thin films . Therefore, Raman data of binary and ternary chalcogenides were used to validate the Raman peak at 198 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Raman data of binary and ternary chalcogenides were used to validate the Raman peak at 198 cm −1 . Table shows the list of Raman modes of various possible chalcogenides . No Raman vibrational mode at 198 cm −1 corresponds to any one of the binary and ternary chalcogenides and hence is attributed to the AZTSe phase.…”
Section: Resultsmentioning
confidence: 99%